Persediaan Lena pada Masa Pandemi Covid-19 di Novotel Bali Nusa Dua & Residences - Ni Kadek Eky Samita; Anak Agung Istri Ratna Sari Wulan; I Wayan Seniartha (Program Studi Manajemen Divisi Kamar, 2023)
The purpose of this study was to determine the supply of flax during the covid-19 pandemic at Novotel Bali Nusa Dua & Residences. The data of this study were obtained by interview and documentation techniques conducted online and the data analysis in this study was descriptive qualitative, namely by analyzing something related to the flax inventory in the Novotel Bali Nusa Dua & Residence Hotel with reference to the theory, namely, according to Rumekso (2001:165), The minimum stock of flax that must be owned by a hotel in its operations is 3 par stock, namely: 1 installed par, 1 dirty par, 1 ready- to-use par. Then compare and analyze with the theory to get a conclusion. The results of this study indicate that the flax supply during the Covid-19 pandemic owned by Novotel Bali Nusa Dua was mostly less with a percentage of 20% due to dirty, torn and broken.